Des films pour analyser le travail et documenter des situations de formation - Marc Durand; Annie Goudeaux; Germain Poizat; Juana Sarmiento Jaramillo (Images du Travail, Travail des Images)
This paper is about film editing for documentation of work practices and training purposes. It illustrates these principles by a practical case: the working activity of bailiffs in a Swiss cantonal office. Training situations designing is based on a prior analysis of bailiffs’ activity, its constraints and its effects, by the mean of observation and video recording of work practices. During films editing, we move away from the faithful presentation of work practice, to account of its typical implicit elements, revealed by the preliminary analysis. The films are built like stories. They are supposed to disturb the viewers by provoking a mimetic engagement at them when viewing the scenes, and a re-enactement – i.e. an experience close to the former working one –. Viewings are also supposed to trigger appropriation of the typical components of activity by the bailiffs, and an expropriation and sharing of them with other professionals, promoting the construction of a community of practice.